LEGAL REGULATION OF ARTIFICIAL INTELLIGENCE AND ROBOTICS: CONCEPTS AND PERSPECTIVES - Aliyev, Tigran T. (Vestnik Tomskogo gosudarstvennogo universiteta. Pravo, 2021)
More recently, the idea of a robot among laypeople was at the level of an "exhibition piece" that had little or no connection to real life, but rather was part of a theoretically possible future. But with the passage of time and the development of technology, artificial intelligence has been introduced into people's everyday lives: smartphones, robots that help and facilitate human life, electronic assistants in various kinds of services. At the same time, the relation-ship between robots and humans is still largely unregulated by law. The probability of unpre-dictable consequences is growing exponentially. In order to reduce the risk of such adverse consequences, the need for legal regulations plays a key role, the content of which is being reviewed and developed by leading lawyers and engineers. The Industrial Revolution changed the very notion of the ways and means of production in the minds of the masses in such a way that the process of robotisation and the introduction of artificial intelligence into various spheres of life became inevitable. Later on it was under-stood that human influence on production process began to decrease noticeably and was re-placed by programs, which with the help of digital algorithms determined behavior of robots and character of artificial intellect thinking. Russian legislation faced the task of legal assess-ment of the nature of artificial intelligence and regulation of its use. The article analyzes possible ways of disclosing the concept "artificial intelligence" as a legal category and its correlation to the concept "robot", deals with questions of legal respon-sibility for the work of artificial intelligence, studies the possibility of recognition of a robot possessing artificial intelligence as a subject of law. Purpose of work is to propose ways of legislation development in conditions of digitalisa-tion and introduction of artificial intelligence in everyday life. The topic of legal regulation of artificial intelligence and robotics is investigated on a scientific basis. The scientific basis of this article was formed on the basis of scientific works of foreign scientists (Higgins T., Musk I., Calo R., Frumkin A.M., Kerr I., Pagallo W., Walker J.). The scientific development of the content of this article was based on general scientific methods: analysis, synthesis, generalization, statistics, induction and deduction, interpretation, classification and comparative methods.